2023
DOI: 10.1007/s00405-023-07995-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of tinnitus and hyperacusis in 9–12-year-old children

Abstract: Objectives To estimate the prevalence of tinnitus and hyperacusis in children aged 9–12 years in Flanders, as well as to explore the associations with hearing abilities and listening behaviours. Design A cross-sectional survey was undertaken in four different Flemish schools. The questionnaire was distributed among 415 children, with a response rate of 97.3%. Results The prevalence of permanent tinnitus was 10.5% and of hyperacusis was 3.3%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The most recent prevalence study identified the estimated prevalence of tinnitus and hyperacusis and associated hearing abilities and listening behaviours in children aged 9–12 years in Flanders [ 15 ]. The study involved a questionnaire distributed to 415 children in four different Flemish schools and determined the prevalence of permanent tinnitus in the sample to be 10.5%.…”
Section: Prevalence Risk Factors and Pathophysiology Of Tinnitus In C...mentioning
confidence: 99%
“…The most recent prevalence study identified the estimated prevalence of tinnitus and hyperacusis and associated hearing abilities and listening behaviours in children aged 9–12 years in Flanders [ 15 ]. The study involved a questionnaire distributed to 415 children in four different Flemish schools and determined the prevalence of permanent tinnitus in the sample to be 10.5%.…”
Section: Prevalence Risk Factors and Pathophysiology Of Tinnitus In C...mentioning
confidence: 99%